Contemporary perspectives on play in early childhood education - Saracho, Olivia N.; Spodek, Bernard (Contemporary perspectives in early childhood education., 2003)
This text looks at how the study of play has gained attention and concerns about play in young children have emerged. Ten chapters examine the understanding of play and its theories, play in school, pre-school and theories of pretence, mental representation and humour development.